Detection of Circulating Tumor Cells in Non-Small Cell Lung Cancer - Hanssen, Annkathrin; Loges, Sonja; Pantel, Klaus; Wikman, Harriet (Frontiers in Oncology, 2015)
Lung Cancer is the most common cause of cancer related deaths that frequently metastasizes prior to disease diagnosis. Circulating tumor cells (CTCs) are found in many different types of epithelial tumors and are of great clinical interest in terms of prognosis and therapy intervention. Here, we present and discuss EpCAM-dependent and -independent capture of CTCs in non-small cell lung cancer (NSCLC) and the clinical relevance of CTC detection and characterization. Taking blood samples and analyzing CTCs as “liquid biopsy” might be a far less invasive diagnostic strategy than biopsies of lung tumors or metastases. Moreover, sequential blood sampling allows to study the dynamic changes of tumor cells during therapy, in particular the development of resistant tumor cell clones.